Pengaruh Motivasi, Lingkungan Kerja, Kepemimpinan Transformasional, Disiplin Kerja Dan Budaya Organisasi Terhadap Kinerja Pegawai Puskesmas Di Kecamatan Adiwerna - Muhammad Ziddan; Sutarmin Sutarmin (CV. ITTC INDONESIA, 2025)
Employee performance is very important for the sustainability of an organization or company because performance can affect employee perspectives. This study aims to analyze the effect of motivation, work environment, transformational leadership, work discipline and organizational culture on the performance of Puskesmas employees in Adiwerna District, to find out whether these factors affect employee performance. The data used in this study are primary data obtained by distributing questionnaires to respondents. The sample in this study was 101 with sampling using probability sampling with the simple random sampling method. Data analysis used multiple linear regression analysis with the help of SPSS v.26. Based on the results of this study, it shows that motivation, work environment, transformational leadership, work discipline and organizational culture have a positive effect on the performance of Puskesmas employees in Adiwerna District.